TEMBANG TRADISIONAL ANGKLUNG UNTUK MENGATASI PERMASALAHANPSIKOLOGIS KHUSUSNYA MASALAH KESEPIAN (LONELINESS) LANSIADITINJAU DARI ANALISIS SPEKTRUM FREKUENSI - Yudi Yudistira, Asep Abdul Syukur, dan Samsul Feri Apriyadi (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
So far angklung traditional songs have been used as entertainment. Those who enjoyed those songsdo not realize that they can be useful for elderly people when listening to the songs. These songs havesoft music that can soothe hearts. This research was aimed at fnding out how angklung traditionalsongs could overcome the loneliness problem among elderly people.The sample was one music sample, and the title of the angklung song was O ina ni keke composedby Suwandi. This choice was based on the instrumental similarities. In this research angklung traditionalsong was used as a variable. The data collection to find out the frequency spectrum started from thesample of angklung songs. The obtained data were 1) initial, middle, and final frequency, 2) averagefrequency of the song, 3) duration of the frequency.The result of the research showed the angklung traditional songs could decrease the level ofloneliness among elderly people were those with the dominant frequency spectrum of bandwith 4‐5 kHzin the middle duration and 3.33‐5 kHz in the initial and final duration.Key words: angklung traditional song, music sample, frequency spectrum